Teaching robot modelling and control with RobLib - Ferreira, N. M. Fonseca (2019)
The paper presents a program for robotics education that runs on standard PC's under the Microsoft Windows environment. The RobLib package is designed for undergraduate students and emphasis the fundamental aspects of robot modelling and control. The software is self-explanatory and uses menus, dialog boxes with figures and context-dependent on-line help. In this perpective, students are motivated to investigate on the workspace, kinematics, dynamics, trajectory planning, position and force control of manipulators. Based on this first experience, further studies on robotics, using more sophisticated packages and concepts, are, then, more attractive from the students point of view.